Long-term neurodegenerative sequelae of concussion: implications for musculoskeletal injury risk and neuromuscular interventions - Wood, Tyler A.; Kamari, Mahgolzahra; Grahovec, Nicholas E.; Wilson, Matthew (Frontiers in Musculoskeletal Disorders, 2025)
Concussions pose significant health risks across the lifespan, with most symptoms typically resolving within four weeks in otherwise healthy adults. However, emerging research suggests that individuals with a history of concussion—even after receiving medical clearance—may face an increased risk of subsequent upper- and lower-extremity musculoskeletal injuries. Additionally, prior concussions have been linked to an elevated risk of osteoarthritis later in life. The 6th Consensus Statement on Concussion in Sport highlights the urgent need for further research into recovery determinants and the long-term neurodegenerative consequences of concussion. This mini-review explores the potential neurodegenerative sequelae following concussion and examines the role of neuromuscular exercise interventions in mitigating these effects. By addressing these concerns, such interventions may help reduce concussion-related injury risks and enhance long-term health outcomes.